The anthropology of Western religions : ideas, organizations, and constituencies - Leaf, Murray J. (Lexington Books, 2014)
The Anthropology of Western Religions: Ideas, Organizations, and Constituencies is a comparative survey of the world's major religious traditions as professional enterprises and, often, as social movements. Documenting the principle ideas behind Western religious traditions from an anthropological perspective, Murray J. Leaf demonstrates how these ideas have been used in building internal organizations that mobilize or fail to mobilize external support. Leaf documents a wide range of cultural and social phenomena and the ways in which they merge, ultimately proposing an anthropological method of promoting cross-cultural understanding that stems from these intersections.